Myt1l haploinsufficiency leads to obesity and multifaceted behavioral alterations in mice - Wöhr, Markus; Fong, Wendy M.; Janas, Justyna; Mall, Moritz; Thome, Christian; Vangipuram, Madhuri; Meng, Lingjun; Südhof, Thomas C.; Wernig, Marius (Molecular autism, 2022)
The zinc finger domain containing transcription factor Myt1l is tightly associated with neuronal identity and is the only transcription factor known that is both neuron-specific and expressed in all neuronal subtypes. We identified Myt1l as a powerful reprogramming factor that, in combination with the proneural bHLH factor Ascl1, could induce neuronal fate in fibroblasts. Molecularly, we found it to repress many non-neuronal gene programs, explaining its supportive role to induce and safeguard neuronal identity in combination with proneural bHLH transcriptional activators. Moreover, human genetics studies found MYT1L mutations to cause intellectual disability and autism spectrum disorder often coupled with obesity.